Obstetrics and gynecology physician knowledge of Rh immune globulin prophylaxis. Issue 6 (16th April 2017) - Yu, Amy; Morris, Erin; Adams, Richard; Fung, Mark K.
Abstract : BACKGROUND: Previous studies have shown that more than 20% of laboratories would have recommended inaccurate doses of Rh immune globulin (RhIG) in hypothetical cases. Efforts have been made in educating laboratories in correct dosing calculations; however, obstetricians are most often responsible for ordering RhIG. The objective of this study was to assess knowledge of RhIG indications and dosing among obstetrics and gynecology (OB/GYN) physicians in the United States. STUDY DESIGN AND METHODS: An anonymous 17‐ question online survey was distributed to all OB/GYN resident and attending physicians affiliated with US residency training programs. RESULTS: A total of 165 surveys were collected, with 139 fully completed. Ninety‐two percent of respondents correctly recognized the need for RhIG in D– patients with negative antibody screens. In a scenario of a fetomaternal hemorrhage (FMH) of 45 mL, only 22% of respondents correctly chose the appropriate RhIG dosage. Of those who were correct, 10% had correctly identified 30 mL as the amount of fetal whole blood covered by one dose of RhIG, while 48% incorrectly identified 15 mL (n = 31). A total of 49.3% of respondents reported residency as the most recent formal training on RhIG dosing and 35% reported never (n = 140). CONCLUSIONS: Our study found that OB/GYN physicians are knowledgeable regarding indications for RhIG immunoprophylaxis but were insufficient at calculating dosages in cases of FMH. More standardized education and training among OB/GYN physicians may decrease the risk of maternal alloimmunization, in part because RhIG dosage recommendations from laboratories are not standard practice.